2003
DOI: 10.1128/jvi.77.12.6692-6699.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Recurrent Ocular Herpes Simplex Virus Type 1 Disease after Therapeutic Vaccination of Latently Infected Mice

Abstract: The potential of therapeutic vaccination of animals latently infected with herpes simplex virus type 1 (HSV-1) to enhance protective immunity to the virus and thereby reduce the incidence and severity of recurrent ocular disease was assessed in a mouse model. Mice latently infected with HSV-1 were vaccinated intranasally with a mixture of HSV-1 glycoproteins and recombinant Escherichia coli heat-labile enterotoxin B subunit (rEtxB) as an adjuvant. The systemic immune response induced was characterized by high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
(43 reference statements)
2
38
0
Order By: Relevance
“…Similarly, providing more antigen to CD8 T cells that are continuously stimulated in vivo and functionally impaired may, in fact, worsen the exhaustion. Indeed, with a recent notable exception (75), therapeutic vaccination has rarely provided benefit when the antigen load is high (32,56,61,126), and most positive results have been achieved when viral replication is suppressed either by drug treatment or latency (52,63,93,114). As with preventive vaccination, the proliferative potential of responding T cells will be an important factor determining the outcome of therapeutic vaccinations (116).…”
Section: Challenges For Preventive and Therapeutic Vaccinesmentioning
confidence: 99%
“…Similarly, providing more antigen to CD8 T cells that are continuously stimulated in vivo and functionally impaired may, in fact, worsen the exhaustion. Indeed, with a recent notable exception (75), therapeutic vaccination has rarely provided benefit when the antigen load is high (32,56,61,126), and most positive results have been achieved when viral replication is suppressed either by drug treatment or latency (52,63,93,114). As with preventive vaccination, the proliferative potential of responding T cells will be an important factor determining the outcome of therapeutic vaccinations (116).…”
Section: Challenges For Preventive and Therapeutic Vaccinesmentioning
confidence: 99%
“…Several studies have examined the potential benefits of therapeutic vaccination during a variety of persistent infections (6,9,15,18,20,22,24,28,30,31,38,40). On one hand, some reports have demonstrated enhanced immune responses following therapeutic vaccination.…”
mentioning
confidence: 99%
“…So, this time and dose were selected to evaluate the effects of acute morphine administration on immune responses to HSV-1 reactivation in the nearest time after acute morphine administration with maximum of immunosuppression. Reactivation of HSV-1 from latency may be closely tied to the effect of glucocorticoids on the immune response (26). It is now clear that opioids have a wide array of immunomodulatory effects on the innate and acquired immune systems through the hypothalamic-pituitary-adrenal axis by increasing glucocorticoid levels (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we use one single dose of 75 mg/kg morphine, based on previous studies that have shown this dose induces maximum immunosuppression in mice (7). Richards et al have shown that HSV reactivation induces cellular immunity 4 to 7 days after reactivation (26). Therefore, in order to prevent interference between the primary immune response and secondary immunity induced during HSV reactivation, the effects of morphine administration on immune responses to HSV-1 reactivation were evaluated quickly (12 h) after the injection of morphine.…”
Section: Discussionmentioning
confidence: 99%